KUALITAS PELAYANAN JASA BENGKEL DALAM MENINGKATKAN KEPUASAN KONSUMEN PADA PT ISTANA MOBIL TRIO MOTOR BANJARMASIN - Rizki Amalia Afriana (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2017)
Abstract,The purpose of this research is to determine the service quality car service by PT Istana Mobil Trio Motor Banjarmasin during this time and to determine customer satisfaction in service at PT Istana Mobil Trio Motor Banjarmasin.This research population is a consumer in 2015. Samples taken as many as 100 consumer respondents with sampeling technique using the formula of Slovin. The method that used in this research is descriptively.The research found out that the services provided so far has been pretty good but there are still some grievances or complaints submitted by consumers as the estimated time to repair the car that can not be predicted, the car wash for the bonus is less clean, the air conditioner in waiting room less cold and are not provided space smoking area, no special identification for service advisors so difficult to be recognized by the consumer.The result of this study is the most variable kind of service is variable assurance, can be viewed on the state of the car is good and complete when submitted after the service (41%), trustworthy and provide a sense of security (47%), employees have good knowledge in answering any questions (45%). While the variable that most the respondents felt unsatisfactory is variable Reliability (reliability), seen from the average response disagree the most, ie (27%) in the statement of timely execution of the car as promised because the percentage is not good, then it is indeed for this indicator should get more attention from the company. Able to overcome the damage of the car, respondent response good is 41 persons (41%) and serious in resolving complaints, respondent respons good is 59 persons (59%), although already well but still must be considered and improved. For already feel quite satisfied with the services provided by the PT Istana Mobil Trio Motor Banjarmasin only there are still some grievances felt by some customers on certain variables that must be improved concluded for other variables such as Tangibles, Responsiveness and Emphaty.